Editorial: "real world data" of AIH—time to connect!. Issue 11 (28th November 2018) - Hupa‐Breier, Katharina Luise; Taubert, Richard; Jaeckel, Elmar; Manns, Michael P.
Abstract : Linked Content This article is linked to Liberal et al paper. To view this article visit https://doi.org/10.1111/apt.13907 .